Islamic Education of the Gowa Sultanate Period - Sonya Elsa Triyanda Pohan; Abd Mukti; S Sapri (Universitas Muhammadiyah Enrekang, 2024)
This research aims to explore and clarify studies related to Islamic education during the Gowa sultanate. This scientific study uses a qualitative method with a type of approach that is based on theories of Islamic education approaches in other supporting fields of science such as sociological and historical approaches so that it also includes an interdisciplinary approach, the data of which refers to field research and is supported by library research. The data used in this study uses secondary data, including accredited journals and books that are appropriate to the topic studied. The results of the analysis concluded that the influx of Islamic teachings was brought by ulama from outside the region and applied knowledge by paying attention to the suitability of the cult culture and customs of different communities in Sulawesi, especially in the Gowa sultanate. In the end, the long and systematic process of the ulama figures in developing Islamic education produced results that have now made him one of the largest adherents of Islam in the archipelago